Metaphors and creativity in architectural design - Hussein Alhmoud, Saeed; Hussein Alhmoud, Husam; Mohammad Bataineh, Anas (project baikal, 2025)
The article is devoted to the study of the relationship between metaphorical thinking and creativity in the field of architectural design. Based on the definition of metaphor as the transfer of an element to another context, the authors list the main types of contexts, the elements of which are most actively used in architecture. Several examples of metaphorical thinking in specific architectural projects are considered. It is concluded that a high degree of creativity is achieved through the informal, archetypal use of metaphors based on deep layers of collective cultural and historical heritage.